2017
DOI: 10.1097/qai.0000000000001190
|View full text |Cite
|
Sign up to set email alerts
|

TALEN-Mediated Knockout of CCR5 Confers Protection Against Infection of Human Immunodeficiency Virus

Abstract: Transcription activator-like effector nuclease (TALEN) represents a valuable tool for genomic engineering due to its single-nucleotide precision, high nuclease activity, and low cytotoxicity. We report here systematic design and characterization of 28 novel TALENs targeting multiple regions of CCR5 gene (CCR5-TALEN) which encodes the co-receptor critical for entry of human immunodeficiency virus type I (HIV-1). By systemic characterization of these CCR5-TALENs, we have identified one (CCR5-TALEN-515) with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 79 publications
0
28
0
Order By: Relevance
“…From previous studies, HIV-1 enters cells via co-receptor CCR5 at the early stage of infection and many studies involving CCR5 disruption have been performed by utilizing gene manipulation tools, such as ZFN, TALEN, and the newly developed CRISPR/Cas9 [ 22 , 33 , 43 , 44 ]. Meanwhile, CXCR4, which may act as a co-receptor for late stage entry and accelerate the progress of the disease [ 34 ], has also been studied [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…From previous studies, HIV-1 enters cells via co-receptor CCR5 at the early stage of infection and many studies involving CCR5 disruption have been performed by utilizing gene manipulation tools, such as ZFN, TALEN, and the newly developed CRISPR/Cas9 [ 22 , 33 , 43 , 44 ]. Meanwhile, CXCR4, which may act as a co-receptor for late stage entry and accelerate the progress of the disease [ 34 ], has also been studied [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…TALENs are also showing promise in other strategies. Like ZFPs, TALENs have been used to knock out the CCR5 gene in cell culture [203][204][205][206], permitting efficient gene editing and protection of cells from HIV infection [207] with minimal off-target activity and low cytotoxicity. TALE-activators, corresponding to TALEs fused to potent transcription activators, have been developed and shown to effectively reactivate latent HIV-1 in cell line models [208][209][210] and in PBMCs from ART-suppressed individuals [210].…”
Section: Talesmentioning
confidence: 99%
“…It has been shown that the presence of multiple sequence repeats in TALEN genes renders them unsuitable cargos for lentiviral vector repeats [81]. However, the single-nucleotide precision give rise to superior editing efficiency with minimal off-target and cytotoxicity effects when compared to ZFNs thereby making TALENs good candidates for sequence-specific genome modification [82].
Fig.
…”
Section: Transcription Activator-like Effector Nucleases (Talens)mentioning
confidence: 99%
“…However, several experimental studies have shown promising results with potential for optimization for large scale anti-HIV-1 treatment. Shi and colleagues recently generated 28 CCR5-TALEN screens to target several domains on the CCR5 of CD4+ T cells [82]. CCR5-ZFNs similar to the anti-HIV-1 ZFNs currently being applied for ongoing clinical trials were used as controls in this study for comparative studies.…”
Section: Transcription Activator-like Effector Nucleases (Talens)mentioning
confidence: 99%